Promoting Critical Reading Strategy in Literacy Based-Writing Instruction: Indonesian Context - Henri Fatkurochman (Universitas Muhammadiyah Jember, 2019)
Teaching writing English as a foreign language (EFL) in university setting aims to achieve both linguistic and literacy competencies. It means that the instruction not only focuses on facilitating students to build writing English proficiency, but also on leading students to become literate. Based on this context, it is important for lecturers to select appropriate and effective strategies in the writing instruction. Critical reading is regarded as meaningful and effective reading strategy which can be applied by academic writing instructors or lecturers in order to enable the students in writing an English-written paper. This article attempts to discuss why and how critical reading strategy should be utilized in literacy model of EFL writing instruction, especially in writing a research paper. By understanding the relationship between reading and writing, it is hoped that the activities in the EFL writing classroom can be more meaningful.